2021
DOI: 10.1177/26344041211007831
|View full text |Cite
|
Sign up to set email alerts
|

Staying alive: A 21st century agenda for mental health, child protection and forensic services

Abstract: Mental health treatment, child protection and forensic services for criminality need major reorganisation in conceptualisation and service provision. This need results from the failure of current diagnostic methods, administrative organisations and treatment approaches to reduce the prevalence of mental illness, child maltreatment or criminal behaviour. We propose that defining these problems as individual deficits and responding to them by category of harm (to self, progeny and others, respectively) stands in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The DMM is an overarching framework through which to understand human adaptability and psychopathology within the context of danger (Crittenden & Landini, 2011; Crittenden, Landini, & Spieker, 2021). This position is consistent with views held by Bowlby and Ainsworth (Landa & Duschinsky, 2013; Duschinsky & Solomon, 2017).…”
Section: Theoretical Predictions and Theory-knitting With The Dmmmentioning
confidence: 99%
“…The DMM is an overarching framework through which to understand human adaptability and psychopathology within the context of danger (Crittenden & Landini, 2011; Crittenden, Landini, & Spieker, 2021). This position is consistent with views held by Bowlby and Ainsworth (Landa & Duschinsky, 2013; Duschinsky & Solomon, 2017).…”
Section: Theoretical Predictions and Theory-knitting With The Dmmmentioning
confidence: 99%
“…We found that the DMM‐AAI (i) differentiated family forensic parents from other adults and (ii) differentiated among family forensic parents, thus suggesting their need for individualised services. The detail of an AAI can contribute to personalised treatment plans (Crittenden, 2016; Crittenden et al ., 2021a; Crittenden et al ., 2021b; Dallos et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…See Figure 1 for a comparison of the Berkeley and DMM models. Table 1 in the accompanying paper (Crittenden et al ., 2021a) gives a description of each DMM strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The DMM‐AAI, like psychiatric diagnosis, requires specialised skills and authorised assessors (Crittenden, Landini & Spieker, 2021). A standardised reliability test is used to establish coder reliability; coders receive a dated certificate from the Family Relations Institute indicating their level of reliability.…”
Section: Trainingmentioning
confidence: 99%